1997
DOI: 10.1523/jneurosci.17-10-03766.1997
|View full text |Cite
|
Sign up to set email alerts
|

A Monosynaptic GABAergic Input from the Inferior Colliculus to the Medial Geniculate Body in Rat

Abstract: The goal was to investigate possible monosynaptic GABAergic projections from the inferior colliculus (IC) to thalamocortical neurons of the medial geniculate body (MGB) in the rat. Although there is little evidence for such a projection in other sensory thalamic nuclei, a GABAergic, ascending auditory projection was reported recently in the cat. In the present study, immunohistochemical and tract-tracing methods were used to identify neurons in the IC that contain GABA and project to the MGB. GABA-positive pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
196
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(208 citation statements)
references
References 43 publications
10
196
2
Order By: Relevance
“…Therefore, it is suggested that LG cells control the entire IC circuit according to global state of brainstem nuclei, while GLU cells control according to the state of specific pathways. LG cells are shown to send long‐range projection to thalamus to elicit inhibitory response faster than excitation (Peruzzi, Bartlett, Smith, & Oliver, 1997). The long‐range connection inside the IC may also cause fast inhibition, which is important for coding complex information such as duration (Casseday et al., 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is suggested that LG cells control the entire IC circuit according to global state of brainstem nuclei, while GLU cells control according to the state of specific pathways. LG cells are shown to send long‐range projection to thalamus to elicit inhibitory response faster than excitation (Peruzzi, Bartlett, Smith, & Oliver, 1997). The long‐range connection inside the IC may also cause fast inhibition, which is important for coding complex information such as duration (Casseday et al., 1994).…”
Section: Discussionmentioning
confidence: 99%
“…All procedures were approved by the Animal Care and Use Committee at the University of Science and Technology of China. Slices containing the MGB were prepared using a procedure similar to that described previously [21,25]. Briefly, the rat was decapitated and the brain was rapidly removed and submerged in ice-cold artificial cerebrospinal fluid (ACSF) containing (in mmol/L) 129 NaCl, 3 KCl, 1.2 KH 2 PO 4 , 1.3 MgSO 4 , 20 NaHCO 3 , 2.4 CaCl 2 , 3 HEPES, and 10 D-glucose at pH 7.3-7.4 (osmolarity: 300-310 mOsm/ kg).…”
Section: Animalsmentioning
confidence: 99%
“…In the rat MGB, 99% of the neurons are glutamatergic [14,15] and receive inhibitory inputs mainly from the inferior colliculus and the thalamic reticular nucleus [16][17][18][19][20]. The inhibitory inputs are distributed across the dorsal and ventral parts of the MGB and evoke inhibitory postsynaptic potentials [16,21] which can hyperpolarize an MGB neuron sufficiently to produce a robust RD [22][23][24]. Although RD is a prominent feature of MGB neurons [4,5], its detailed physiological characteristics have not been described.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, data from the somatosensory thalamus show that TRN axonal projections display a well-focused terminal field (Pinault and Deschênes 1998). Last, the auditory thalamus of rodent has Ͻ1% of local interneurons Larue 1988, 1996), but the inhibitory inputs coming from the inferior colliculus (Peruzzi et al 1997;Saint Marie et al 1997; can potentially shape the functional properties of MG neurons. More precisely, it is possible that for some MGv cells, the balance between the excitatory and inhibitory inputs coming from the inferior colliculus exerts a major control on the breadth of tuning and threshold.…”
Section: Tonotopic Organization Of the Trn-mg Connectionsmentioning
confidence: 99%
“…The somatosensory thalamus and the auditory thalamus possess 20 -25% of inhibitory interneurons in primate and cat (Benson et al 1991; Fitzpatrick et al 1984;Montero 1989;Penny et al 1983; Spreafrico et al 1983) but Ͻ1% in rat Larue 1988, 1996). In the auditory thalamus (medial geniculate nucleus, MG) of rat and cat, an additional source of GABAergic inhibition is directly provided by the sensory inputs coming from the inferior colliculus (Peruzzi et al 1997;Saint Marie et al 1997;.…”
Section: Introductionmentioning
confidence: 99%